GENDER STEREOTYPES IN INSTAGRAM COMMENTS: A SOCIOLINGUISTIC ANALYSIS OF LANGUAGE USE - Erlianti, Dira; Zasrianita, Fera; Andriadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social media has become an important communication space where users construct identities, express opinions, and negotiate social meanings through language. Within this environment, gender stereotypes continue to emerge while also being challenged through user interactions. This study aims to analyze how language use in Instagram comments reflects and challenges gender stereotypes from a sociolinguistic perspective. A descriptive qualitative approach was employed using 150 English-language comments collected from 15 posts on the Instagram account @therock through purposive sampling. The data were gathered through digital documentation and analyzed using the interactive model by Miles, Huberman, and Saldaña, which includes data collection, data condensation, data display, and conclusion drawing and verification. The findings reveal two dominant patterns of language use. Some comments reinforce traditional gender stereotypes by portraying men as protectors and symbols of strength, while women are represented as emotionally expressive and family-oriented. In contrast, other comments challenge these stereotypes through men’s expressions of emotional vulnerability and appreciation, as well as women’s encouragement of men’s health awareness and the sharing of personal experiences. These findings indicate that Instagram comments function not only as a medium of social interaction but also as a dynamic space where gender meanings are continuously reproduced and negotiated through language.